Numerical solution of the thermomechanical processes in the thin layer structure of thermal barrier - Kuneš, Josef; Veselý, Zdeněk (Computer Assisted Methods in Engineering and Science, 2023)
High demands for dynamic thermal insulating protection of machine parts lead to the development of thermal barriers. The mathematical and simulation model has been developed to simulate thermomechanical processes during thermal shock on the surface of different thermal barrier structures. The finite element method has been applied to the heterogeneous thin layer structure of the thermal barrier. Temperature, temperature gradient, heat flux, thermally induced stress and strain have been chosen as the characteristics describing the dynamic behaviour of the thermal barrier during the thermal shock. Results of the simulation for several alternatives of thermal barrier are discussed to summarize the effect of characteristic parameters of the thermal barrier to its dynamic behaviour.